US Presidents and Cold War Nuclear Diplomacy, Aiden Warren & Joseph M Siracusa - Raheela Kokab (CISS Insight Journal, 2024)
“US Presidents and Cold War Nuclear Diplomacy” offers a comprehensive analysis of the intricate relationship between American presidents and the complex world of nuclear diplomacy during the Cold War era. Written by Aiden Warren and Joseph M Siracusa, scholars in the field of international relations, the book takes readers on a captivating journey through the critical moments that defined US nuclear policy from the aftermath of the Second World War to the end of the Cold War.The book’s central theme revolves around the critical role played by different US presidents during the Cold War era. The authors meticulously explore American foreign policies concerning the Soviet Union, emphasizing the complex dynamics of nuclear diplomacy, nuclear armament, and power balancing patterns that characterized this tumultuous period. The book focuses mainly on the nuclear arms race, ideological conflict, and non-proliferation efforts between the US and the USSR.